2019
DOI: 10.1021/acscatal.9b02167
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Isolation between Turnovers on Au18 Nanoclusters: Formic Acid Decomposition One Molecule at a Time

Abstract: Formic acid (HCOOH or FA) is a clean, safe, and renewable hydrogen storage material. Although Au catalysts decompose vapor-phase FA with high activity and selectivity towards hydrogen, the active site and reaction mechanism remain unclear. Here, we show that the subnanometric Au18 cluster (0.8 nm in diameter) is likely the active species for FA decomposition. We performed coverage self-consistent, density functional theory-based kinetic Monte Carlo simulations of FA decomposition on gas-phase Au18 clusters, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 90 publications
1
26
0
Order By: Relevance
“…The other carboxyl (COOH) pathway leads to the formation of CO, [19] which is against the experimental observations. All energetics were evaluated at infinite separation; although previous studies showed that lateral interactions between adsorbates may significantly affect the energetics of FA decomposition on small clusters, [20] coadsorption of the intermediates does not significantly impact the trends identified in our work (Figure S29). The resulting potential energy diagrams are shown in Figure 7 c; energies of the studied intermediates and transition states are tabulated in Table S5.…”
Section: Resultsmentioning
confidence: 63%
“…The other carboxyl (COOH) pathway leads to the formation of CO, [19] which is against the experimental observations. All energetics were evaluated at infinite separation; although previous studies showed that lateral interactions between adsorbates may significantly affect the energetics of FA decomposition on small clusters, [20] coadsorption of the intermediates does not significantly impact the trends identified in our work (Figure S29). The resulting potential energy diagrams are shown in Figure 7 c; energies of the studied intermediates and transition states are tabulated in Table S5.…”
Section: Resultsmentioning
confidence: 63%
“…Next, we probed the reaction energetics of FA decomposition over both Pd 13 and Pd 8 Mn 5 O(OH) 13 .Out of the two main FA decomposition pathways,w eo nly considered the formate (HCOO À )p athway.T he other carboxyl (COOH) pathway leads to the formation of CO, [19] which is against the experimental observations.A ll energetics were evaluated at infinite separation;a lthough previous studies showed that lateral interactions between adsorbates may significantly affect the energetics of FA decomposition on small clusters, [20] coadsorption of the intermediates does not significantly impact the trends identified in our work ( Figure S29). The resulting potential energy diagrams are shown in Figure 7c; energies of the studied intermediates and transition states are tabulated in Table S5.…”
Section: Angewandte Chemiementioning
confidence: 67%
“… Kinetic Isolation between Turnovers on Au 18 Nanoclusters: Formic Acid Decomposition One Molecule at a TimeChenB. W. J.StamatakisM.MavrikakisM. Chen, B. W. J. Stamatakis, M. Mavrikakis, M. ACS Catal.2019994469457 …”
Section: Key Referencesmentioning
confidence: 99%
“…Combination of DFT-derived mean-field MKMs and reaction kinetics experiments on Au/SiC, led to the conclusion that Au 18 might resemble the active site the best. Kinetic Monte Carlo (KMC) study on Au 18 revealed that a pair of adjacent Au 3 ensembles (coordination number (CN) of 5), can be the active site for FA decomposition on Au/SiC (ref ).…”
Section: Fa Decomposition On Supported Gold Catalystsmentioning
confidence: 99%
See 1 more Smart Citation